High-entropy transparent ceramic as well as preparation method and application thereof
By preparing (LuxYySczYbmErn) 2O3 high-entropy transparent ceramics, using ball mill mixing and vacuum pressure-free sintering, the problems of high-entropy transparent ceramics are solved, and the preparation of high-performance ceramics is realized, which is suitable for nuclear energy window materials.
Patent Information
- Application Number
- CN202411954237.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The existing high entropy transparent ceramics have high temperature or require pressure sintering, and their optical properties are average, and other properties are rarely reported, making it difficult to meet the high temperature stability and radiation resistance requirements of nuclear reactor observation window materials.
Using a high entropy transparent ceramic formula of (LuxYySczYbmErn)2O3, the mixture was mixed, dried, ground, and sieved by ball mill, and calcined at 800-1200°C to obtain a mixed powder, which was then sintered under vacuum without pressure, and finally annealed and polished.
The prepared high entropy transparent ceramics have high relative density, good optical, mechanical, corrosion-resistant and radiation-resistant properties, and are suitable for the application of nuclear energy window materials.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of transparent ceramics, and more specifically, relates to a high-entropy transparent ceramic and a preparation method and application thereof. Background Art
[0002] Most nuclear reactor observation windows are made of glass, which is brittle and has poor high temperature resistance. Magnesium-aluminum spinel has good stability in high temperature environments and excellent mechanical properties, and is a material with application potential in nuclear reactors. In recent years, it has been considered as a window material for nuclear fusion systems, but it will produce radiation damage (i.e., color centers) after irradiation, and its radiation resistance needs to be improved.
[0003] Rare earth oxide transparent ceramics have low neutron absorption cross-section, high melting point, wide optical transparency zone, high mechanical strength and hardness, thermal shock resistance and chemical corrosion resistance. High entropy was originally defined in solid solution metal alloys of five or more elements, and later introduced into high entropy ceramics. Since the minimization of Gibbs free energy controls the thermodynamic stability of the material, high configurational entropy can make ceramic materials have higher thermodynamic stability at high temperatures. In addition, compared with traditional ceramic materials, high entropy ceramics exhibit superior mechanical properties, corrosion resistance, thermal properties and radiation resistance. However, the existing high entropy transparent ceramics have high preparation temperatures (>1850℃) or require pressure sintering, only focusing on their optical properties, and the optical quality is general, and other properties are rarely reported. Summary of the invention
[0004] In order to solve the above technical problems, the primary purpose of the present invention is to provide a high entropy transparent ceramic having good mechanical properties, corrosion resistance and radiation resistance.
[0005] Another object of the present invention is to provide a method for preparing the above-mentioned high entropy transparent ceramic.
[0006] Another object of the present invention is to provide applications of the high entropy transparent ceramic.
[0007] The purpose of the present invention is achieved through the following technical solutions:
[0008] A high entropy transparent ceramic has the molecular formula (Lu x Y y Sc z Yb m Er n )2O3, wherein 0.05≤x≤0.6, 0.05≤y≤0.6, 0.05≤z≤0.6, 0.05≤m≤0.6, 0.05≤n≤0.6, and x+y+z+m+n=1.
[0009] Preferably, the high entropy transparent ceramic is prepared by mixing Lu2O3 powder, Y2O3 powder, Sc2O3 powder, Yb2O3 powder, Er2O3 powder and sintering aid ZrO2 powder by ball milling, drying, grinding, sieving, and calcining at 800-1200°C to obtain a mixed powder; the mixed powder is molded into a green blank, which is pressurelessly sintered at 1600-1800°C under vacuum, and then polished after annealing at 1000-1300°C.
[0010] Preferably, the relative density of the high entropy transparent ceramic is above 99.5%, the transmittance in the visible light region (1000 nm) is above 76%, and the optical properties change little after irradiation.
[0011] Preferably, the particle size of the Lu2O3 powder, Y2O3 powder, Sc2O3 powder, Yb2O3 powder and Er2O3 powder is 5-20 μm, the purity of the Lu2O3 powder, Y2O3 powder, Sc2O3 powder, Yb2O3 powder and Er2O3 powder is above 99.99%, the particle size of the ZrO2 powder is 0.2-0.4 μm, and the purity of the ZrO2 powder is above 99.9%.
[0012] Preferably, the atomic proportion of Zr in the ZrO2 powder is 0.1 to 5 at.% of Lu, Y, Sc, Yb and Er in Lu2O3 powder, Y2O3 powder, Sc2O3 powder, Yb2O3 powder and Er2O3 powder.
[0013] Preferably, the ball mill is a planetary ball mill, anhydrous ethanol and ZrO2 grinding balls are added, the diameter of the ZrO2 grinding balls is 2-3 mm, the rotation speed of the ball mill is 200-300 r / min, and the ball milling time is 20-48 h; the total mass of Lu2O3 powder, Y2O3 powder, Sc2O3 powder, Yb2O3 powder, Er2O3 powder and ZrO2 powder, the mass ratio of anhydrous ethanol and ZrO2 grinding balls is 1:(2-4):(4-8).
[0014] The method for preparing the high entropy transparent ceramic comprises the following steps:
[0015] S1. Lu2O3 powder, Y2O3 powder, Sc2O3 powder, Yb2O3 powder, Er2O3 powder and sintering aid ZrO2 powder are mixed by ball milling, dried, crushed, sieved, and calcined at 800 to 1200 ° C to obtain a mixed powder;
[0016] S2. The mixed powder is dry pressed and then cold isostatically pressed to obtain a green blank, which is heated to 1600-1800°C for pressureless sintering under vacuum, and then annealed at 1000-1300°C and polished to obtain (Lu x Y y Sc z Yb m Er n)2O3 high entropy transparent ceramics, wherein 0.05≤x≤0.6, 0.05≤y≤0.6, 0.05≤z≤0.6, 0.05≤m≤0.6, 0.05≤n≤0.6, and x+y+z+m+n=1.
[0017] Preferably, in step S1, the drying temperature is 60-80° C., the drying time is 12-24 hours, and the calcination time is 2-4 hours.
[0018] Preferably, the pressure of the cold isostatic pressing in step S2 is 150-300 MPa, the holding time of the cold isostatic pressing is 5-10 min; the vacuum degree of the vacuum is 10 -4 ~10 -3 Pa; the heating rate is 10 to 15°C / min, the pressureless sintering time is 6 to 24 hours, and the annealing time is 2 to 10 hours.
[0019] The application of the high entropy transparent ceramic in the field of preparing nuclear energy window materials.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] 1. The present invention prepares (Lu x Y y Sc z Yb m Er n The relative density of )2O3 high entropy transparent ceramics is above 99.5%, and the transmittance at 1000nm is above 76%. It has high relative density, good optical, mechanical, corrosion resistance and radiation resistance, and can be used in the preparation of nuclear energy window materials.
[0022] 2. The present invention adopts vacuum pressureless sintering to form a multi-component solid solution at a lower temperature to prepare (Lu x Y y Sc z Yb m Er n )2O3 high entropy transparent ceramics. The process is simple, the production cost is low, and it is easy to achieve mass production. DETAILED DESCRIPTION
[0023] The content of the present invention is further described below in conjunction with specific examples, but it should not be construed as limiting the present invention. If not specifically indicated, the technical means used in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0024] Example 1
[0025] 1. Mix Lu2O3 powder, Y2O3 powder, Sc2O3 powder, Yb2O3 powder and Er2O3 powder in a molar ratio of 2:3:1:2:2 with 0.5at.% sintering aid ZrO2 powder (the atomic proportion of Lu, Y, Sc, Yb and Er in Lu2O3 powder, Y2O3 powder, Sc2O3 powder, Yb2O3 powder and Er2O powder is 0.5at.%), add anhydrous ethanol solvent and ZrO2 grinding balls (diameter 2mm), the total mass of Lu2O3, Y2O3, Sc2O3, Yb2O3, Er2O3 powder and ZrO2 powder, the mass ratio of ethanol and ZrO2 grinding balls is 1:2:6, the ball mill speed is 250r / min, the ball mill time is 20h, dry, grind, sieve, and calcine at 1000℃ for 4h to obtain a mixed powder.
[0026] 2. After dry pressing of the mixed powder, cold isostatic pressing at 200 MPa was performed with a holding time of 5 min to obtain a green blank. -3 Under vacuum, the temperature was raised to 1300℃ at a rate of 10℃ / min, then raised to 1800℃ at a rate of 5℃ / min, kept at this temperature for 8h, then lowered to 800℃ at a rate of 10℃ / min and then cooled in the furnace. Annealing at 1200℃ in air for 4h and polishing to obtain high entropy transparent ceramics with the molecular formula (Lu 0.2 Y 0.3 Sc 0.1 Yb 0.2 Er 0.2 )2O3.
[0027] The (Lu 0.2 Y 0.3 Sc 0.1 Yb 0.2 Er 0.2 The relative density of 2O3 high entropy transparent ceramics is 99.72%, the transmittance at 1000nm is 78.6%, the hardness is 8.5GPa, and the toughness is 1.2MPa·m 1 / 2 After irradiation with 18MeV protons, the ceramic transmittance changed slightly, decreasing by only 6%.
[0028] Example 2
[0029] 1. Mix Lu2O3 powder, Y2O3 powder, Sc2O3 powder, Yb2O3 powder and Er2O3 powder in a molar ratio of 2:1.5:2.5:2:2 with 2at.% sintering aid ZrO2 powder (Zr in ZrO2 powder is Lu2O3 powder, Y2O3 powder, Sc2O3 powder, Yb2O3 powder and Er2O powder, and the atomic proportion of Lu, Y, Sc, Yb and Er is 2at.%), add anhydrous ethanol and ZrO2 grinding balls (diameter 3mm), the total mass of Lu2O3, Y2O3, Sc2O3, Yb2O3, Er2O3 powder and ZrO2 powder, the mass ratio of ethanol and ZrO2 grinding balls is 1:3:5, the ball milling speed is 300r / min, the ball milling time is 20h, dry, grind and sieve. Calcinate at 900℃ for 4h to obtain a mixed powder.
[0030] 2. After dry pressing of the mixed powder, cold isostatic pressing at 250MPa was performed with a holding time of 5min to obtain a green blank. -4 Under vacuum, the temperature was raised to 1300℃ at a rate of 10℃ / min, then raised to 1700℃ at a rate of 5℃ / min, kept at this temperature for 10h, and then lowered to 800℃ at a rate of 10℃ / min and then cooled in the furnace. Annealing at 1200℃ in air for 4h and polishing to obtain high entropy transparent ceramics with the molecular formula (Lu 0.2 Y 0.15 Sc 0.25 Yb 0.2 Er 0.2 )2O3.
[0031] The (Lu 0.2 Y 0.15 Sc 0.25 Yb 0.2 Er 0.2 The relative density of 2O3 high entropy transparent ceramics is 99.93%, the transmittance at 1000nm is 80.3%, the hardness is 9.2GPa, and the toughness is 1.4MPa·m 1 / 2 After irradiation with 18MeV protons, the ceramic transmittance changed slightly, decreasing by only 5%.
[0032] Example 3
[0033] 1. Mix Lu2O3 powder, Y2O3 powder, Sc2O3 powder, Yb2O3 powder and Er2O3 powder in a molar ratio of 1.5:2.5:2.5:2:1.5 with 2at.% ZrO2 powder (Zr in ZrO2 powder is Lu2O3 powder, Y2O3 powder, Sc2O3 powder, Yb2O3 powder and Er2O powder, and the atomic proportion of Lu, Y, Sc, Yb and Er in Lu2O3 powder, Y2O3 powder, Sc2O3 powder, Yb2O3 powder and Er2O powder is 2at.%), add anhydrous ethanol and ZrO2 grinding balls (diameter 2mm), the total mass of Lu2O3, Y2O3, Sc2O3, Yb2O3, Er2O3 powder and ZrO2 powder, the mass ratio of ethanol and ZrO2 grinding balls is 1:2:6, the ball milling speed is 280r / min, the ball milling time is 26h, dry, grind and sieve. Calcinate at 900℃ for 4h to obtain a mixed powder.
[0034] 2. After dry pressing of the mixed powder, cold isostatic pressing at 300MPa was performed with a holding time of 5min to obtain a green blank. -3 Under vacuum, the temperature was raised to 1300°C at a rate of 10°C / min, then raised to 1650°C at a rate of 5°C / min, kept at this temperature for 15h, then lowered to 800°C at a rate of 10°C / min, and then cooled in the furnace. Annealing was performed at 1100°C in air for 4h, and then polished to obtain a high entropy transparent ceramic with the molecular formula (Lu 0.25 Y 0.15 Sc 0.25 Yb 0.2 Er 0.15 )2O3.
[0035] The (Lu 0.25 Y 0.15 Sc 0.25 Yb 0.2 Er 0.15 )2O3 high entropy transparent ceramics have a relative density of 99.98%, a transmittance of 81.6% at 1000nm, a hardness of 9.8GPa, and a toughness of 1.6MPa·m 1 / 2 After irradiation with 18MeV protons, the ceramic transmittance changed slightly, decreasing by only 3%.
[0036] Example 4
[0037] 1. Mix Lu2O3 powder, Y2O3 powder, Sc2O3 powder, Yb2O3 powder and Er2O3 powder in a molar ratio of 3:1.5:2:1.5:2 with 2at.% ZrO2 powder (Zr in ZrO2 powder is Lu2O3 powder, Y2O3 powder, Sc2O3 powder, Yb2O3 powder and Er2O powder, and the atomic proportion of Lu, Y, Sc, Yb and Er in Lu2O3 powder, Y2O3 powder, Sc2O3 powder, Yb2O3 powder and Er2O powder is 2at.%), add anhydrous ethanol and ZrO2 grinding balls (diameter 2mm), the total mass of Lu2O3, Y2O3, Sc2O3, Yb2O3, Er2O3 powder and ZrO2 powder, the mass ratio of ethanol and ZrO2 grinding balls is 1:3:6, the ball milling speed is 250r / min, the ball milling time is 36h, dry, grind and sieve. Calcinate at 1000℃ for 4h to obtain a mixed powder.
[0038] 2. After dry pressing of the mixed powder, cold isostatic pressing at 150MPa was performed with a holding time of 5min to obtain a green blank. -4 Under vacuum, the temperature was raised to 1300℃ at a rate of 15℃ / min, then raised to 1600℃ at a rate of 5℃ / min, kept at this temperature for 6h, then lowered to 800℃ at a rate of 10℃ / min and then cooled in the furnace. After annealing at 1200℃ in air for 4h, high entropy transparent ceramics were obtained by polishing. The molecular formula is (Lu 0.3 Y 0.15 Sc 0.2 Yb 0.15 Er 0.2 )2O3.
[0039] The (Lu 0.3 Y 0.15 Sc 0.2 Yb 0.15 Er 0.2 The relative density of 2O3 high entropy transparent ceramics is 99.86%, the transmittance at 1000nm is 79.4%, the hardness is 8.9GPa, and the toughness is 1.28MPa·m 1 / 2 After irradiation with 18MeV protons, the ceramic transmittance changed slightly, decreasing by only 5%.
[0040] Example 5
[0041] 1. Mix Lu2O3 powder, Y2O3 powder, Sc2O3 powder, Yb2O3 powder and Er2O3 powder in a molar ratio of 3:2:1.5:1.5:2 with 1at.% ZrO2 powder (Zr in ZrO2 powder is Lu2O3 powder, Y2O3 powder, Sc2O3 powder, Yb2O3 powder and Er2O powder, and the atomic proportion of Lu, Y, Sc, Yb and Er is 1at.%), add anhydrous ethanol and ZrO2 grinding balls (diameter 2mm), the total mass of Lu2O3, Y2O3, Sc2O3, Yb2O3, Er2O3 powder and ZrO2 powder, the mass ratio of ethanol and ZrO2 grinding balls is 1:2:5, the ball milling speed is 260r / min, the ball milling time is 48h, dry, grind and sieve. Calcinate at 1200℃ for 4h to obtain a mixed powder.
[0042] 2. After dry pressing of the mixed powder, cold isostatic pressing at 200 MPa was performed with a holding time of 5 min to obtain a green blank. -3 Under vacuum, the temperature was raised to 1300℃ at a rate of 10℃ / min, then raised to 1700℃ at a rate of 5℃ / min and kept at that temperature for 20h, then lowered to 800℃ at a rate of 10℃ / min and then cooled in the furnace. After annealing at 1000℃ in air for 4h, high entropy transparent ceramics were obtained by polishing. The molecular formula is (Lu 0.3 Y 0.2 Sc 0.15 Yb 0.15 Er 0.2 )2O3.
[0043] The (Lu 0.3 Y 0.2 Sc 0.15 Yb 0.15 Er 0.2 The relative density of 2O3 high entropy transparent ceramics is 99.96%, the transmittance at 1000nm is 80.9%, the hardness is 9.4GPa, and the toughness is 1.3MPa·m 1 / 2 After irradiation with 18MeV protons, the ceramic transmittance changed slightly, decreasing by only 4%.
[0044] The high entropy transparent ceramic of the present invention has a relative density of more than 99.5%, a transmittance of more than 76% at 1000nm, a hardness of more than 8.45GPa, and a toughness of 1.2MPa·m 1 / 2 As shown above, after 18MeV proton irradiation, the ceramic transmittance changes slightly, with a decrease of less than 6%. It has good optical, mechanical, corrosion resistance and radiation resistance properties and can be used in the field of preparing nuclear energy window materials.
[0045] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A high entropy transparent ceramic, characterized in that: The molecular formula of the high entropy transparent ceramic is (Lu x Y y Sc z Yb m Er n )2O3, wherein 0.05≤x≤0.6, 0.05≤y≤0.6, 0.05≤z≤0.6, 0.05≤m≤0.6, 0.05≤n≤0.6, and x+y+z+m+n=1.
2. The high entropy transparent ceramic according to claim 1, characterized in that: The high entropy transparent ceramic is prepared by mixing Lu2O3 powder, Y2O3 powder, Sc2O3 powder, Yb2O3 powder, Er2O3 powder and sintering aid ZrO2 powder by ball milling, drying, grinding and screening, and calcining at 800-1200°C to obtain a mixed powder; the mixed powder is molded into a green blank, and the green blank is pressurelessly sintered at 1600-1800°C under vacuum, and then polished after annealing at 1000-1300°C.
3. The high entropy transparent ceramic according to claim 1, characterized in that: The high entropy transparent ceramic has a relative density of more than 99.5% and a transmittance in the visible light region of more than 76%.
4. The high entropy transparent ceramic according to claim 2, characterized in that: The particle sizes of the Lu2O3 powder, Y2O3 powder, Sc2O3 powder, Yb2O3 powder and Er2O3 powder are all 5-20μm, and the purity of the Lu2O3 powder, Y2O3 powder, Sc2O3 powder, Yb2O3 powder and Er2O3 powder is all above 99.99%. The particle size of the ZrO2 powder is 0.2-0.4μm, and the purity of the ZrO2 powder is above 99.9%.
5. The high entropy transparent ceramic according to claim 2, characterized in that: The atomic proportion of Lu, Y, Sc, Yb and Er in the ZrO2 powder, Lu2O3 powder, Y2O3 powder, Sc2O3 powder, Yb2O3 powder and Er2O3 powder is 0.1 to 5 at.%.
6. The high entropy transparent ceramic according to claim 2, characterized in that: The ball mill is a planetary ball mill, anhydrous ethanol and ZrO2 grinding balls are added, the diameter of the ZrO2 grinding balls is 2-3 mm, the rotation speed of the ball mill is 200-300 r / min, and the ball milling time is 20-48 h; the total mass of Lu2O3 powder, Y2O3 powder, Sc2O3 powder, Yb2O3 powder, Er2O3 powder and ZrO2 powder, the mass ratio of anhydrous ethanol and ZrO2 grinding balls is 1:(2-4):(4-8).
7. The method for preparing a high entropy transparent ceramic according to any one of claims 1 to 6, characterized in that: The steps include: S1. Lu2O3 powder, Y2O3 powder, Sc2O3 powder, Yb2O3 powder, Er2O3 powder and sintering aid ZrO2 powder are mixed by ball milling, dried, crushed, sieved, and calcined at 800 to 1200 ° C to obtain a mixed powder; S2. The mixed powder is dry pressed and then cold isostatically pressed to obtain a green blank, which is heated to 1600-1800°C for pressureless sintering under vacuum, and then annealed at 1000-1300°C and polished to obtain (Lu x Y y Sc z Yb m Er n )2O3 high entropy transparent ceramics, wherein 0.05≤x≤0.6, 0.05≤y≤0.6, 0.05≤z≤0.6, 0.05≤m≤0.6, 0.05≤n≤0.6, and x+y+z+m+n=1.
8. The method for preparing high entropy transparent ceramics according to claim 7, characterized in that: In step S1, the drying temperature is 60-80° C., the drying time is 12-24 hours, and the calcination time is 2-4 hours.
9. The method for preparing the high entropy transparent ceramic according to claim 7, characterized in that: The pressure of the cold isostatic pressing in step S2 is 150-300 MPa, and the holding time of the cold isostatic pressing is 5-10 min; the vacuum degree of the vacuum is 10 -4 ~10 - 3 Pa; the heating rate is 10 to 15°C / min, the pressureless sintering time is 6 to 24 hours, and the annealing time is 2 to 10 hours.
10. Application of the high entropy transparent ceramic according to any one of claims 1 to 6 in the field of preparing nuclear energy window materials.
Citation Information
Patent Citations
Method of manufacturing transparent sesquioxide sintered body, and transparent sesquioxide sintered body manufactured by the method
CN103708839A
Luminescence enhanced Tm<3+>-doped Lu2O3-based transparent ceramic and preparation method thereof
CN106588014A
Up-conversion luminescence enhanced transparent ceramic and application thereof in improving photoelectric conversion efficiency of crystalline silicon solar cells
CN109020544A
Transparent ceramic, manufacturing method thereof, and magneto-optical device
CN110240480A
Transparent ceramics, manufacturing method thereof, and magneto-optical device
EP3536676A1
Cited By
Preparation method of high-entropy rare earth silicate ceramic powder and block and ceramic powder
CN118771887A